Identifying and managing fraudulent participants: critical commentary from a qualitative study with older adults. - Rees, Jessica; Liu, Wei; Tinker, Anthea; Matcham, Faith (Critical Public Health, 2025)
We recently published findings from our qualitative study exploring the lived experiences of loneliness in later life to inform technology development. During recruitment for this study, we experienced the significant and emerging issue in qualitative research of fraudulent participants. This involved the same participant attempting to be interviewed multiple times to obtain monetary gain. By providing specific examples from our experience, we aim to raise awareness of this timely issue for the research community. We also present practical and actionable recommendations for the readership of this journal to address the methodological challenges of fraudulent participation in online qualitative interview studies.